Exosomes in postshock mesenteric lymph are key mediators of acute lung injury triggering the macrophage activation via Toll‐like receptor 4. Issue 1 (29th August 2017) - Kojima, Mitsuaki; Gimenes‐Junior, Joao A.; Chan, Theresa W.; Eliceiri, Brian P.; Baird, Andrew; Costantini, Todd W.; Coimbra, Raul
Abstract : Acute lung injury (ALI) is a common cause of morbidity in patients after severe injury due to dysregulated inflammation, which is believed to be driven by gut‐derived inflammatory mediators carried via mesenteric lymph (ML). We have previously demonstrated that nano‐sized extracellular vesicles, called exosomes, secreted into ML after trauma/hemorrhagic shock (T/HS) have the potential to activate immune cells in vitro. Here, we assess the function of ML exosomes in the development of T/HS‐induced ALI and the role of TLR4 in the ML exosome‐mediated inflammatory response. ML exosomes isolated from rats subjected to T/HS stimulated NF‐KB activation and caused proinflammatory cytokine production in alveolar macrophages. In vivo experiments revealed that intravenous injection of exosomes harvested after T/HS, but not before shock, caused recruitment of inflammatory cells in the lung, increased vascular permeability, and induced histologic ALI in naive mice. The exosome‐depleted supernatant of ML had no effect on in vitro and in vivo inflammatory responses. We also demonstrated that both pharmacologic inhibition and genetic knockout of TLR4 completely abolished ML exosome‐induced cytokine production in macrophages. Thus, our findings define the critical role of exosomes secreted into ML as a critical mediator of T/HS‐induced ALI through macrophage TLR4 activation.—Kojima, M., Gimenes‐Junior, J. A., Chan, T. W., Eliceiri, B. P., Baird, A., Costantini, T. W., Coimbra, R. Exosomes in postshock mesenteric lymph are key mediators of acute lung injury triggering the macrophage activation via Toll‐like receptor 4. FASEB J. 32, 97‐110 (2018). www.fasebj.org